2005
DOI: 10.1158/0008-5472.can-05-2262
|View full text |Cite
|
Sign up to set email alerts
|

Headpin: A Serpin with Endogenous and Exogenous Suppression of Angiogenesis

Abstract: Headpin is a novel serine proteinase inhibitor (serpin) with constitutive mRNA expression in histologically normal oral mucosa but with lost or down-regulated expression in head and neck squamous cell carcinoma. Several serpin family members are similarly lost in multiple cancer types and hold tumor suppressor functions including the inhibition of angiogenesis. However, the functional significance for the loss of headpin expression in cancer is not known. Using immunohistochemical analysis of invasive squamous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
25
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 29 publications
3
25
0
Order By: Relevance
“…A number of serpin members have been identified as endogenous angiogenic inhibitors (20)(21)(22)(23). Some of these serpin angiogenic inhibitors have also displayed anti-inflammatory activities (38).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of serpin members have been identified as endogenous angiogenic inhibitors (20)(21)(22)(23). Some of these serpin angiogenic inhibitors have also displayed anti-inflammatory activities (38).…”
Section: Discussionmentioning
confidence: 99%
“…However, a number of natural antiangiogenic factors or angiogenic inhibitors have been identified (18). The identified angiogenic inhibitors include several serine proteinase inhibitors (SERPIN), such as pigment epithelium-derived factor (PEDF), α1-antitrypsin (AAT), maspin, SERPINA3K, and headpin (19)(20)(21)(22)(23)(24)(25).…”
mentioning
confidence: 99%
“…Most serpins act as inhibitors of chymotrypsin-like SPs, others as cross-class serine protease inhibitors of papain-like cysteine proteases and caspases (10)(11)(12)(13). Certain serpins have been identified to be involved in the progression of malignant tumor; these include SERPINB3 and SERPINB4 in squamous cell carcinoma (14,15), SERPINB5 in human breast cancer (16), SERPINB13 in head and neck squamous cell carcinoma (17), SERPINH1 in head and neck carcinomas (18), SERPINI2 in breast cancer (19), SERPINB2 and SERPINE1 in breast cancer and other cancers (20), and SERPINB2, SERPINB3, SERPINB4, SERPINB7, SERPINB11, SERPINB12 and SERPINB13 in oral squamous cell carcinoma (21).…”
Section: Introductionmentioning
confidence: 99%
“…In oral carcinoma, Xia et al suggested that higher SERPINB5 expression was significantly associated with better overall survival (11). Furthermore, down-regulated expression of the SERPINB13 (headpin/ hurpin) gene has been demonstrated in head and neck malignancies (12)(13)(14). Both SERPINB5 and SERPINB13 genes are located on chromosome 18q, which is the location of the serpin gene cluster and other members of serpin family.…”
Section: Introductionmentioning
confidence: 99%